Green HRM Practices to Improve Environmental Performance through Green Culture in Employees PT. Industri Pangan in Mojokerto - Handayani, Trisna Duwi; Kusmaningtyas, Amiartuti; Mujanah, Siti (PT Inovasi Pratama Internasional, 2025)
This research aims to analyze Green HRM Practices to improve Environmental Performance through Green Culture among PT Food Industry in Mojokerto. Green HRM integrates traditional HR functions such as recruitment, training, performance management, and employee engagement with environmentally conscious practices to foster cultural sustainability and environmental performance within an organization. The research method used in this research is a quantitative approach. The data collection technique used was a survey using a questionnaire instrument. The population used was 940 employees, the sample used was 90 employees using Slovin calculations, and the sampling technique used was Random Sampling. The data analysis technique uses path analysis with the help of SmartPLS 4 software. The research results show that the Green HRM Practices variable has a significant effect on Green Culture. The Green Culture variable has no significant effect on Environmental Performance. The Green HRM Practices variable has a significant effect on Environmental Performance. The Green HRM Practice variable on Environmental Performance with Green Culture as a mediator has no significant influence on PT Food Industry in Mojokerto. Variables that are proven to have a more dominant influence are at least retained, if possible, they can be improved.